Conventional oxygen therapy versus CPAP as a ceiling of care in ward-based patients with COVID-19: a multi-centre cohort evaluation. (October 2021) - Bradley, P; Wilson, J; Taylor, R; Nixon, J; Redfern, J; Whittemore, P; Gaddah, M; Kavuri, K; Haley, A; Denny, P; Withers, C; Robey, RC; et al.
ABSTRACT: Background: Continuous positive airway pressure (CPAP) therapy is commonly used for respiratory failure due to severe COVID-19 pneumonitis, including in patients deemed not likely to benefit from invasive mechanical ventilation (nIMV). Little evidence exists demonstrating superiority over conventional oxygen therapy, whilst ward-level delivery of CPAP presents practical challenges. We sought to compare clinical outcomes of oxygen therapy versus CPAP therapy in patients with COVID-19 who were nIMV. Methods: This retrospective multi-centre cohort evaluation included patients diagnosed with COVID-19 who were nIMV, had a treatment escalation plan of ward-level care and clinical frailty scale ≤ 6. Recruitment occurred during the first two waves of the UK COVID-19 pandemic in 2020; from 1 st March to May 31 st, and from 1 st September to 31 st December. Patients given CPAP were compared to patients receiving oxygen therapy that required FiO2 ≥0. 4 for more than 12 hours at hospitals not providing ward-level CPAP. Logistic regression modelling was performed to compare 30-day mortality between treatment groups, accounting for important confounders and within-hospital clustering. Findings: Seven hospitals provided data for 479 patients during the UK COVID-19 pandemic in 2020. Overall 30-day mortality was 75.6% in the oxygen group (186/246 patients) and 77.7% in the CPAP group (181/233 patients). A lack of evidence for a treatment effect persisted in the adjusted model (adjusted odds ratio 0.84 95% CI 0.57-1.23, p=0.37). 49.8% of patients receiving CPAP-therapy (118/237) chose to discontinue it. Interpretation: No survival difference was found between using oxygen alone or CPAP to treat patients with severe COVID-19 who were nIMV. A high patient-initiated discontinuation rate for CPAP suggests a significant treatment burden. Further reflection is warranted on the current treatment guidance and widespread application of CPAP in this setting. Funding: L Pearmain is supported by the MRC (MR/R00191X/1). TW Felton is supported by the NIHR Manchester Biomedical Research Centre.